IDENTITAS PEREMPUAN DALAM KELUARGA BERDASARKAN KANJI PEREMPUAN - Harisal; Wahyuning Dyah; Kanah; Ni Nyoman Mastiani Nadra , (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Female is the most common gender in Japanese kanji. Its role in society can be seen in the interpretation of the kanji for women. The purpose of this research is to describe the women’s identity in the family based on the kanji for women. To describe the identity of women in the family, the research method used is a descriptive-qualitative method. The population in this study is all Japanese kanji which are a combination of bushu female kanji, with the sample in this study being kanji that use female bushu which means women in the family. The data is taken from the kanji for women with female identities based on the kanji found in Nelson's kanji dictionary. The results of the study show that women in the family cannot be separated from their identity as women in the concept ie in Japan who have the nature to marry, get pregnant, give birth, and take care of the house. Based on the phonetic depiction of the kanji, which means women in the family using the bushu kanji for women, it can be seen that the concept of ie is indeed very influential on the identity of Japanese women who have duties and responsibilities to take care of the household